CRENÇAS DE PROFESSORES DOS ANOS INICIAIS DO ENSINO FUNDAMENTAL ACERCA DO SEU PAPEL NO DESENVOLVIMENTO DOS LETRAMENTOS - Schizzi, Barbara (2024)
This research seeks to understand teachers' beliefs about their role in developing their students' of literacies. There was like general objective was to investigate the beliefs of teachers in the 4th and 5th year of elementary school at CAIC school, regarding its role in the development of literacies. The development of literacy is fundamental for the comprehension of written materials and also for the social use of reading and writing. Therefore, working with literacy at school is important. And this research aims to contribute to the formation of teachers, trying to help them reflect on their beliefs about literacy. Our research consists of a case study, whose data collection was carried out through interviews with participants. Data analysis was carried out using the Appraisal Theory, which is divided into three subsystems: attitude, engagement and gradation. In this research we use attitude as a basis, which is subdivided into categories, which are: affection, judgment and appreciation. The interviews with the four teachers who agreed to participate in the study were recorded in audio/video and the recordings were transcribed manually, respecting the way the words were pronounced, but pauses, intonation, hesitation and other forms of sound expression were not transcribed. Analyzing the responses from the interviews based on the Appraisal Theory, firstly, it was possible to conclude that the teachers used the appreciation category more times. In relation to appreciation, the teachers evaluated more the concept of literacy, its practice, the importance of its role and the learning of the students. The second most used category was judgment, the ones that received the most judgment evaluations were students and their learning, families, work and the role of the teacher. And the least used category was affection, which was more related to the work of the teacher and the experiences of the students. After this analysis of the interviews, some beliefs emerged, such as that teachers understand literacy as a broader process than teaching to read and write, that they believe that their work is very important for the development of their students' literacy and that they face many challenges in this work, which makes it even more challenging. These observed beliefs are very important and need to be discussed among teachers in their continuing education process.